Azoarcus halotolerans sp. nov., a novel member of Rhodocyclaceae isolated from activated sludge collected in Hong Kong. Issue 11 (18th November 2020) - Li, Shuyang; Zhao, Lin; Han, Jingyi; Liu, Shuangyuan; Dai, Jingcheng; Fu, Guiping; Qiu, Dongru
Abstract : A floc-forming bacterial strain, designated HKLI-1 T, was isolated from the activated sludge of a municipal sewage treatment plant in Hong Kong SAR, PR China. Cells of this strain were Gram-stain-negative, strictly aerobic, catalase- and oxidase-positive, rod-shaped and motile by means of a single polar flagellum. Growth occurred at 18–37 °C (optimum, 28 °C), pH 5.5–9.0 (optimum, pH 7.5) and with 0–8.0 % (w/v) NaCl (optimum, 1–1.5 %) concentration. The major fatty acids of strain HKLI-1 T were C16 : 0 and summed feature 3 (C16 : 1  ω7 c and/or C16 : 1  ω6 c ). The polar lipid profile contained diphosphatidylglycerol, phosphatidylethanolamine, phosphatidylglycerol and three unidentified lipids. The DNA G+C content was 63.5 mol% from whole genomic sequence analysis. Based on the results of 16S rRNA gene sequences analysis, this strain should be assigned to the genus Azoarcus and is closely related to Azoarcus olearius DQS-4 T (94.93 % 16S rRNA gene sequence pairwise similarity), Azoarcus toluclasticus MF63 T (94.91 %) and Azoarcus communis SWub3 T (94.01 %), but separate from them by large distances in different phylogenetic trees. Based on whole genome analysis, the orthologous average nucleotide identity and in silico DNA–DNA hybridization values against four of the closest relatives were 73.03–74.83 and 17.2–23.0 %, respectively. The phylogenetic, genotypic, phenotypic and chemotaxonomic data demonstrated that strain HKLI-1 T could be distinguished from its phylogenetically related species, and that this strain represented a novel species within the genus Azoarcus, for which the name Azoarcus halotolerans sp. nov. is proposed. The type strain is HKLI-1 T (= 72659 T =CCTCC AB 2019312 T ).